The intergenerational legacy of early-life malnutrition during the great leap forward famine in China - Han Zhang; Wing Chung Ho (BMC Public Health)
Abstract Background Parents’ early-age experiences may influence their life-course trajectories and potentially also affect the wellbeing of their offspring. There is an emerging body of literature on the intergenerational legacy of early childhood malnutrition. In this study, we examined whether and to what extent parental exposure to the 1959 China Famine associated with themselves and their children’s outcomes. We differentiated exposures to famine at different stages (prenatal and childhood) of parents’ life course. Method Using the 2010 China Family Panel Study (CFPS) data, this study applied the Difference-in-differences (DID) approach to examine the consequences of famine exposure. Results Our analysis showed that mothers who experienced famine during their prenatal period were more likely to have lower socioeconomic outcomes and that their children were disadvantaged in terms of annual income and monthly salary. Fathers no matter born in pre-famine cohort or famine cohort are not associated with their socioeconomic outcomes, and the intergenerational consequences of famine on the economic outcomes of offspring do not appear to be conveyed along the paternal line. For health outcomes, however, the results showed that parental exposure to famine was not associated with children’s health condition. Conclusion Our study extends the literature regarding Baker’s hypothesis by providing the empirical evidence of the long-term intergenerational legacy of famine. Furthermore, the study enriches the empirical relevance of the intergenerational mobility research from the life-course perspective. Finally, the evidence of this study also offers policy implications for addressing the persistence of intergenerational inequality and poverty caused by early-life shocks.